(untitled) (Saptagandaki Journal, 2017)
Bank is one of the major institutions in the financial sector of any economy. Banking sector plays a vital role as a financial intermediary in the economic development of the country. Among those factors, impact of employee participation on job satisfaction, employee fairness perception and organizational commitment, is also considered as one of the most important factors that improves the performance of commercial banks. This study deals with the fundamental issues associated with the impact of employee participation on job satisfaction, employee fairness perception and organizational commitment of commercial banks of Nepal. In selecting the most reliable and representative samples, stratified sampling techniques was used. The population of the commercial banks was stratified as joint ventures, non-joint ventures and public banks. 15 commercial banks were selected as the sample. The total number of observations used for this study is 200 which include 70 observations from the joint venture banks, 110 observations from the non-joint venture banks and 20 observations from the public banks. Impact of employee participation on job satisfaction, employee fairness perception and organizational commitment have positive significant relation. Among all three determinants organizational commitment is more influenced by employee participation as it has highest correlation coefficient. Most of the surveyed employees agreed that management gives recognition for job performance and they are satisfied with the freedom in work; every employee has opportunity to get promotion in bank, and they are willing to put in a great deal of effort beyond expected in order to help the organization to be successful. The Saptagandaki Journal Vol.8 2017: 1-13